An Exploratory Study of Employee Engagement in Human Service Agencies - Nina Esaki; Xiaofang Liu; Rosemary Vito (Journal of Human Services)
Given research suggesting that engaged employees demonstrate greater workplace performance, employee engagement has been one of the highest trending topics in the management and human resource literature over the past 20 years; yet there is minimal empirical research focused specifically on employee engagement in nonprofit organizations. The purpose of this study was to explore antecedent factors that contribute to employee engagement in the human services sector, using a convenience sample of staff in human service agencies in the New York City region. Organizational trust, satisfaction with supervisor, and coworker support were significant predictors of employee engagement.